Dlaczego elitarne szkoły nie znikną? O nieusuwalności nierówności społecznych w edukacji = Why will elite schools not disappear? On the indelibility of social inequalities in education - Mikiewicz, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Contemporary Polish education faces a rapid change connected with the expansion of schooling on the secondary and the tertiary level. Right after this process there arises an illusion of democratic schooling. Secondary schools, till these days perceived as a pathway to university as well as elite professional and social positions, are open for pupils from the entire social spectrum.
Keywords: Ziemia Lubuska - czasopisma; czasopisma polskie; czasopisma lokalne; czasopismo naukowe